Public Trust and Corporate Transparency in Shaping Corporate Reputation Through Corporate Image - Ade Kurniawan; Ricardo Indra (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: In an increasingly transparent digital business environment, Public Trust and Corporate Transparency have emerged as critical antecedents of Corporate Reputation. However, prior studies have predominantly examined these variables as direct determinants of reputation, with limited attention to Corporate Image as a mediating mechanism, particularly in state-owned enterprises (SOEs) in emerging economies. Objective: This study aims to examine the influence of Public Trust and Corporate Transparency on Corporate Reputation, with Corporate Image acting as a mediating variable, in the context of PT Pupuk Kalimantan Timur. Methods: This study utilizes Structural Equation Modeling (SEM) through WarpPLS, relying on primary data gathered from 400 participants. The primary data were obtained through an online survey disseminated via Pupuk Kaltim's official Instagram account. Results: The results show that both Public Trust and Corporate Transparency have a significant positive effect on Corporate Image, and Corporate Image, in turn, has a significant effect on Corporate Reputation. However, the direct effects of Public Trust and Corporate Transparency on Corporate Reputation were found to be insignificant. The mediation analysis confirms that Corporate Image plays a significant mediating role, indicating that Public Trust and Corporate Transparency influence Corporate Reputation primarily through the formation of a positive Corporate Image. Overall, these findings emphasize that Corporate Reputation is largely shaped by trust-based perceptions and transparent corporate practices that are consolidated through consistent and credible corporate image management. Conclusion: This study highlights the strategic importance of aligning trust-building and transparency initiatives with image